INFLUENCE OF COOPERATIVE SOCIETIES IN PROMOTING FINANCIAL INCLUSION IN THE PREVAILING ECONOMIC HARDSHIP IN NIGERIA (Journal of the Management Sciences, 2024)
The study investigated the influence of cooperative societies in promoting financial inclusion in the prevailing economic hardship in Nigeria. Two hypotheses were formulated and tested at 0.05 level of significance. The Research design adopted for the study was correlational research design. The population of the study comprised members of cooperative societies in Anambra State. The sample of the study comprised 200 members of cooperative societies in Anambra State which was arrived at through multistage sampling technique. The instruments for data collection were two standardized questionnaires. The data collected from the pilot test was tested using Cronbach Alpha. This yielded a reliability coefficient of 0.87 for the first instrument while the second instrument yielded a reliability co-efficient value of 0.85.Pearson Product Moment correlation was used to test the hypotheses. Finding of the study revealed that cooperative societies promotefinancial literacy and digital literacy for financial inclusion among members in the prevailing economic hardship in Nigeria. The researcher therefore recommended among others that Government should provide increased support to cooperative societies through funding, technical assistance, and capacity-building programmes.
Keywords: Cooperative Societies, Financial Inclusion, Financial Literacy, Digital Literacy, Economic Hardship